The last ranger : a novel - Heller, Peter, 1959- (Alfred A. Knopf, 2023)
"Ren is a park ranger, tasked with duties both mundane and thrilling: breaking up fights at campgrounds, saving tourists from moose attacks, and attempting to broker an uneasy peace between the wealthy vacationers who tromp around with cameras and the locals who want to carve out a meaningful living amid this western landscape. When Ren discovers his friend Hilly, a biologist and wolf expert, nearly dead in the steel jaws of a wolf trap, he hopes it's just an accident, but the small red ribbon tied to the stake makes him fairly certain that it wasn't. What begins as an inquiry into a known poacher soon opens into the discovery of a local group of ranchers who have formed an alliance at odds with both the park and with Ren's responsibility to protect it." --